2016
DOI: 10.1080/15384101.2016.1170261
|View full text |Cite|
|
Sign up to set email alerts
|

Pro-fibrotic pathway activation in trabecular meshwork and lamina cribrosa is the main driving force of glaucoma

Abstract: While primary open-angle glaucoma (POAG) is a leading cause of blindness worldwide, it still does not have a clear mechanism that can explain all clinical cases of the disease. Elevated IOP is associated with increased accumulation of extracellular matrix (ECM) proteins in the trabecular meshwork (TM) that prevents normal outflow of aqueous humor (AH) and has damaging effects on the fine mesh-like lamina cribrosa (LC) through which the optic nerve fibers pass. Applying a pathway analysis algorithm, we discover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 64 publications
2
40
0
Order By: Relevance
“…This suggests that TGFβ2 signaling occurs in the TM and optic nerve MTZ of glaucomatous eyes, hence promoting tissue remodeling and/or fibrosis. This is consistent with previous studies (Tamm and Fuchshofer, ; Tovar‐Vidales et al, ; Zode et al, ; Zhavoronkov et al, ). Additionally, Gal3 may also respond to glaucomatous stress in the eye, but this relationship is not entirely clear, as our correlation was not statistically significant.…”
Section: Discussionsupporting
confidence: 93%
“…This suggests that TGFβ2 signaling occurs in the TM and optic nerve MTZ of glaucomatous eyes, hence promoting tissue remodeling and/or fibrosis. This is consistent with previous studies (Tamm and Fuchshofer, ; Tovar‐Vidales et al, ; Zode et al, ; Zhavoronkov et al, ). Additionally, Gal3 may also respond to glaucomatous stress in the eye, but this relationship is not entirely clear, as our correlation was not statistically significant.…”
Section: Discussionsupporting
confidence: 93%
“…Enormous evidence suggests that there is an aberrant accrual of ECM components in TM, AH, ONH, and lamina cribrosa (LC) attributing to the pathology in glaucoma. [29][30][31][32] Tenon's fibroblasts are the primary effector cells in the initiation and mediation of wound healing and fibrotic scar formation posttrabeculectomy. 33 In our gene and protein expression study, we found evident elevations of genes, that is, MCP-1, CTGF, TGF-b1/2, LOX, LOXL2, ELN, COL1A1, SPARC, and a-SMA compared with cataract control in POAG and PACG.…”
Section: Discussionmentioning
confidence: 99%
“…8). MMPs play a central role in ECM turnover, which reduces resistance to aqueous outflow and can serve as a counter-mechanism to IOP elevation (Zhavoronkov et al, 2016). In light of above studies, it is likely that caveolins and the PI3K-Akt pathway plays a pivotal role in TM physiology and contribute to the pathogenesis of POAG and OHT.…”
Section: Pathway Analysis and Functional Annotationmentioning
confidence: 99%